Chapter 8 The BRCA patent controversies - van Zimmeren, Esther (Genetics and Society, 2014)
The discovery of the two inherited susceptibility genes BRCA1 and BRCA2 in the mid-1990s created the possibility of predictive genetic testing and led to the establishment of specific medical programmes for those at high risk of developing breast cancer in the UK, US and Europe. The book provides a coherent structure for examining the diversity of practices and discourses that surround developments linked to BRCA genetics, and to the evolving field of genetics more broadly. It will be of interest to students and scholars of anthropology, sociology, history of science, STS, public health and bioethics. Chapter 8 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9780415824064_oachapter8.pdf